Predictors of Medical Students’ Adoption of Emergency Medicine Virtual Simulation Platforms - Lingjiao Tang; Yu Ning; Hui Lv; Xuebin Li; Aihe Tang (IEEE Access)
Emergency medicine virtual simulation platforms have transformed student training, allowing students to engage with a variety of realistic and replicable emergency scenarios. However, the completion and pass rates are low. The aim of this study is to explore the factors influencing medical students’ adoption of intelligent virtual simulation platforms in China via Technology Acceptance Model 3. A total of 819 medical students from southern Chinese universities participated in the study. Structural equation modeling is used to examine data from cross-sectional quantitative surveys. The results revealed that image, relevance, and result demonstrability significantly affected perceived usefulness, whereas computer self-efficacy, perceptions of external control, anxiety, perceived enjoyment, and playfulness shaped perceived ease of use. Subjective norms emerged as the strongest predictor of behavioral intention, despite not significantly influencing perceived usefulness. The combined influence of subjective norms, perceived usefulness, and perceived ease of use positively affected students’ behavioral intentions. These findings highlight the importance of establishing supportive environments and designing user-friendly virtual simulation tools to promote technology adoption in medical education. These insights can help educational institutions and policymakers integrate virtual simulations effectively into medical curricula, thereby providing better flexible and personalized training experiences, which enhance the quality of skills acquisition and accessibility of emergency medical training.